تحليل قدرة الطالبات في تطبيق القواعد اللغوية عند المحادثة اليومية في الصف الثاني في المرحلة الثانوية بمعهد نور العلم فيراوانج رياو - Afifa Rahmasari, Afifa; Wagiman Manik, Wagiman; Muhajirah Binti Jamaluddin, Muhajirah (Tashdiq: Jurnal Kajian Agama dan Dakwah, 2025)
This research focuses on analyzing the ability of female students to apply linguistic rules in daily conversation at the secondary level at Nurul Ilmi Islamic Boarding School Perawang Riau. The approach in this research is sufficient. The result that was reached was that the students understood the study of grammar, such as grammar and morphology, and they had a high score for each assignment. But in applying linguistic rules in daily conversation, it reaches the level of “good”. What is meant is that the students’ ability to practice using linguistic rules progresses slowly from year to year, and when the researcher conducted a direct investigation in this area, few of them used and retained the correct language rules that they learned in the classroom. But most of them are unable to use linguistic rules when speaking Arabic in the linguistic environment.